Effect of encapsulation agents on antioxidant activity and moisture content of spray dried powder from Mahkota Dewa fruit extract - M. N., Kathiman; Siti Kholijah, Abdul Mudalip; Jolius, Gimbun (IOP Publishing, 2020)
Mahkota Dewa is rich in bioactive compounds including mangiferin, saponin and polyphenols. This work aims to investigate the encapsulation of Mahkota Dewa by spray drying using different types of encapsulation agent. A subcritical water extraction process was used to extract the bioactive compounds from dried Mahkota Dewa prior to spray drying process. The encapsulation agents used were maltodextrin (MT), arabic gum (AG) and mixture of arabic gum-maltodextrin (AG-MT). The spray drying conditions namely inlet dry air temperatures, dry air flow rate and inlet feed flowrate were 200°C, 3.7 m/s and 485 mL/h, respectively. The spray dried powder samples were evaluated for antioxidant activity and moisture content and compared with those without encapsulation agent. A high value of antioxidant activity and low moisture content were observed for samples with encapsulation agents. Result suggested the maltodextrin produced particles with the lowest moisture content (4.84 %) and highest antioxidant activity (94.22%), thus can be recommended as the most suitable encapsulation agent in this work.